Entre itinéraires et trajets : représentations des déplacements dans les guides de voyage au tournant du XIXe siècle - Ariane Devanthéry (In Situ)
An itinerary is more than a route: it is a selected route, chosen by a time and lined with knowledge and emotions. As the Grand Tour had known some strongly coded itineraries, how does the transition to tourism happen? Smoothly or with a crash? Is then a giving up of all itineraries, new ways invented, or redefinition? And what if the Grand Tour converting into tourism was also been acted in the way of displaying the travelling space?